Design and Build Wireless Relay with Electricity Monitoring Based on Internet of Things - Made Toby Sathya Pratika; I Nyoman Piarsa; Anak Agung Ketut Agung Cahyawan Wiranatha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2021)
Electricity is a power source to run various electronic devices. Problem that often occurs is that users forget to turn off or turn on their electronic devices, then prepaid and postpaid electricity users cannot monitoring the electrical power usage of their electronic devices in realtime. The designed device to overcome these problems has a working principle like a switch, but there has relays and several sensors. Controlling electronic devices can be done by user using main switch in designed device, switch button and timer feature in Android application, then user can also monitoring the voltage, current and power in realtime on Android application. The results of several tests that have been done show that the designed device and Android applications that have been built can run well, but the current reading generated by the designed device are still not perfect, adjustments are needed so power calculation is better. Keywords : Android, Control, Electricity, IoT, Monitor